INNOVATIONS IN STUDENT MANAGEMENT IN CHARACTER BUILDING FOR STUDENTS AT THE ASKHABUL KAHFI ISLAMIC BOARDING SCHOOL IN SEMARANG - Rizka Amalia; Sofa Muthohar; Nur Asiyah (Tadbir: Jurnal Manajemen Pendidikan Islam, 2025)
This study aims to describe the innovation of student management in character building at Pondok Pesantren Ashhabul Kahfi Semarang. This research employed a qualitative approach, with data collected through interviews, observations, and documentation. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing. The findings indicate that character formation is implemented through three main programs: Muhasabah wa Tarbiyah, Muhadharah, and the persuasive approach. The Muhasabah wa Tarbiyah program serves as a routine evaluation to foster discipline and responsibility. The Muhadharah program develops students’ courage, communication skills, and social competence. Meanwhile, the persuasive approach is applied in disciplinary guidance, where sanctions function as educational consequences and forms of responsibility rather than punitive measures. These findings emphasize that the integration of student management and Islamic educational values can produce effective character building that is relevant to modern educational challenges. Keywords: Student management, Character education, Pesantren, Innovation